ERS noninvasive ventilation course: basic concepts. Issue 2 (June 2017) - Schönhofer, Bernd; Hart, Nicholas; Scala, Raffaele; van den Biggelaar, Ries; Idrees, Farah
In 2007, the European Respiratory Society (ERS) delivered the Noninvasive Ventilation (NIV) course in Hannover, Germany, for the first time. This teaching course was to become the birth of a successful tradition in the delivery of NIV education by ERS. In the following 10 years, the Hannover NIV course has been held on four occasions, in 2009, 2011, 2014 and, just recently in 2017. Each of these courses have been fully booked with around 80 delegates. Such was the popularity of the course and the rapidly expanding knowledge in this area of acute NIV and home mechanical ventilation (HMV) that, in 2014, the ERS agreed to deliver both a "basic concepts" and an "advanced concepts" course. The Hannover NIV course focused on the basic concepts, whereas the NIV course held for the first time in November 2015 in Milan, Italy, focused on advanced concepts. Faculty and delegates of the @ERStalk course on basic concepts in NIV describe their experiences http://ow.ly/zUPn30b7jLb